Gestión cultural y su incidencia en el turismo local en el gad municipal del cantón la mana, 2023. - Chiliquinga Pusay, Liseth Estefania (2025)
This research analyzes cultural management and its impact on local tourism in the GAD Municipal del Cantón La Maná during the year 2023. The study focused on evaluating three fundamental aspects: the level of visitors' perception of cultural events, financial and technological resource management practices, and the degree of community participation in cultural activities. The methodology employed combined quantitative and qualitative approaches, including surveys of visitors and local stakeholders, as well as interviews with the management of the Department of Education and Culture. The results reveal a moderately favorable perception of cultural events, with 47% acceptance and 73% recognition of the representation of local traditions. In terms of resource management, an organized structure was identified that combines the municipal budget with strategic alliances, although with limitations in terms of technological modernization and financial sustainability. Community participation reached 62% of active involvement, showing opportunities for improvement in communication channels and inclusion strategies. The study concludes that there are solid foundations in the cultural management of the canton, but it is necessary to strengthen key aspects such as the quality of events, technological modernization and community participation to effectively promote local tourism. The recommendations point towards the implementation of innovative strategies to guarantee the sustainability of cultural initiatives in the territory.